Oligomerization of ZFYVE27 (Protrudin) is necessary to promote neurite extension. - D V Krishna Pantakani; Marta M Czyzewska; Anna Sikorska; Chiranjeevi Bodda; Ashraf U Mannan (PLoS ONE, 2011)
ZFYVE27 (Protrudin) was originally identified as an interacting partner of spastin, which is most frequently mutated in hereditary spastic paraplegia. ZFYVE27 is a novel member of FYVE family, which is implicated in the formation of neurite extensions by promoting directional membrane trafficking in neurons. Now, through a yeast two-hybrid screen, we have identified that ZFYVE27 interacts with itself and the core interaction region resides within the third hydrophobic region (HR3) of the protein. We confirmed the ZFYVE27's self-interaction in the mammalian cells by co-immunoprecipitation and co-localization studies. To decipher the oligomeric nature of ZFYVE27, we performed sucrose gradient centrifugation and showed that ZFYVE27 oligomerizes into dimer/tetramer forms. Sub-cellular fractionation and Triton X-114 membrane phase separation analysis indicated that ZFYVE27 is a peripheral membrane protein. Furthermore, ZFYVE27 also binds to phosphatidylinositol 3-phosphate lipid moiety. Interestingly, cells expressing ZFYVE27(ΔHR3) failed to produce protrusions instead caused swelling of cell soma. When ZFYVE27(ΔHR3) was co-expressed with wild-type ZFYVE27 (ZFYVE27(WT)), it exerted a dominant negative effect on ZFYVE27(WT) as the cells co-expressing both proteins were also unable to induce protrusions and showed cytoplasmic swelling. Altogether, it is evident that a functionally active form of oligomer is crucial for ZFYVE27 ability to promote neurite extensions.